Assessing the validity, responsiveness and meaningfulness of the Hidradenitis Suppurativa Clinical Response (HiSCR) as the clinical endpoint for hidradenitis suppurativa treatment. (11th November 2014) - Kimball, A.B.; Jemec, G.B.E.; Yang, M.; Kageleiry, A.; Signorovitch, J.E.; Okun, M.M.; Gu, Y.; Wang, K.; Mulani, P.; Sundaram, M.
Summary Background Quantification of disease severity supports the development of evidence‐based treatments. Assessments to capture clinical improvement in hidradenitis suppurativa (HS) can be improved. Objectives This study aimed to validate the Hidradenitis Suppurativa Clinical Response (HiSCR), which is defined as a ≥ 50% reduction in inflammatory lesion count (sum of abscesses and inflammatory nodules, AN), and no increase in abscesses or draining fistulas in HS when compared with baseline as a meaningful clinical endpoint for HS treatment. Methods Patients with ≥ 3 ANs at baseline in a Phase II adalimumab trial for HS were included for analysis. HiSCR achievers vs. nonachievers were assessed at week 16 and week 52. Criteria measures included physician‐rated assessments [Hurley stage, modified Sartorius score (MSS), and HS Physician's Global Assessment] and patient‐reported outcomes (PROs: visual analogue pain scale, Dermatology Life Quality Index, and Work Productivity and Activity Impairment questionnaire). Test–retest reliability, convergent validity, responsiveness and predictive validity of HiSCR, and its meaningfulness to patients were assessed. Results Among 138 eligible study participants, the majority were female (69·6%) with a mean age of 36·7 years. The mean (median) MSS was 125·2 (85·5) at baseline. Test–retest reliability of the AN count was 0·91. HiSCR was significantly correlated with improvements in all physician‐rated and PRO measures (Spearman's rho between −0·61 and −0·27, all P < 0·001). Improvements of all PROs in HiSCR achievers exceeded the respective meaningful improvement thresholds. Conclusions In patients with HS with ≥ 3 ANs, HiSCR achievers had significant improvements in physician‐rated and patient‐reported HS disease severity and impact. HiSCR is a valid and meaningful endpoint for assessing HS treatment effectiveness in controlling inflammatory manifestations in this population.